Singularities in physics and engineering : properties, methods, and applications - Senthilkumaran, Paramasivam (IOP (Series). Release 5., 2018)
Singularities are pervasive throughout nature and this book is one of the first to combine all aspects of singular optics and to give a detailed view of the subject. Singularities in Optical Physics and Engineering give a thorough introduction to singularities and their development and goes on to explain in detail important topics such as the types of singularities, their properties, detection and application and the emerging research trends that are still developing. The book concentrates mostly on phase singularities in a comprehensive development to allow a greater understanding of singularities throughout the chapters. It also discusses polarization singularities in its final chapter giving an in-depth description of this subject. With new advances being generated continuously, this book will cover a vibrant field of optics and will give an essential foundation to any students and researchers interested in singular optics. Part of IOP Series in Advances in Optics, Photonics and Optoelectronics